(untitled) - United States. Congress; Office of Technology Assessment (Montclair, 1981)
A study by the Office of Technology Assessment (OTA) that identifies and evaluates the "economic, political, and military costs and benefits that accrue to the United States in its trade with the Soviet Union, Eastern Europe, and the People's Republic of China, taking account of the complex ways in which these factors interrelate
Keywords: Thương mại Đông - Tây,East-West trade